Dynamic Changes in High-Sensitivity Cardiac Troponin I in Response to Anthracycline-Based Chemotherapy. Issue 5 (May 2020) - Tzolos, E.; Adamson, P.D.; Hall, P.S.; Macpherson, I.R.; Oikonomidou, O.; MacLean, M.; Lewis, S.C.; McVicars, H.; Newby, D.E.; Mills, N.L.; Lang, N.N.; Henriksen, P.A.
Abstract: Aims: Treatment advances have improved cancer-related outcomes and shifted interest towards minimising long-term iatrogenic complications, particularly chemotherapy-related cardiotoxicity. High-sensitivity cardiac troponin I (hs-cTnI) assays accurately quantify very low concentrations of plasma troponin and enable early detection of cardiomyocyte injury prior to the development of myocardial dysfunction. The profile of hs-cTnI in response to anthracycline-based treatment has not previously been described. Materials and methods: This was a multicentre prospective observational cohort study. Female patients with newly diagnosed invasive breast cancer scheduled to receive anthracycline-based (epirubicin) chemotherapy were recruited. Blood sampling was carried out before and 24 h after each cycle. Hs-cTnI concentrations were measured using the Abbott ARCHITECT STAT assay. Results: We recruited 78 women with a median (interquartile range) age of 52 (49–61) years. The median baseline troponin concentration was 1 (1–4) ng/l and the median cumulative epirubicin dose was 394 (300–405) mg/m 2 . Following an initial 33% fall 24 h after anthracycline dosing ( P  < 0.001), hs-cTnI concentrations increased by a median of 50% ( P  < 0.001) with each successive treatment cycle. In total, 45 patients had troponin measured immediately before the sixth treatment cycle, 21 (46.6%) of whom had hs-cTnI concentrations ≥16 ng/l, indicating myocardial injury. Plasma hs-cTnI concentrations before the second treatment cycle were a strong predictor of subsequent myocardial injury. Conclusions: Cardiotoxicity arising from anthracycline therapy is detectable in the earliest stages of breast cancer treatment and is cumulative with each treatment cycle. This injury is most reliably determined from blood sampling carried out before rather than after each treatment cycle. Highlights: Plasma hs-cTnI concentrations showed an anthracycline dose-dependent increase. Hs-cTnI could act as an early and sensitive anthracycline cardiotoxicity prediction tool. Hs-cTnI measurement should happen before rather than after each cycle.